2011
DOI: 10.3758/s13420-011-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind in dogs: is the perspective-taking task a good test?

Abstract: Udell, Dorey, and Wynne (in press) have reported an experiment in which wolves, shelter dogs, and pet dogs all showed a significant preference for begging from a person who faced them (seer) over a person whose back was turned to them (blind experimenter). On tests with the blind person's eyes covered with a bucket, a book, or a camera, pet dogs showed more preference for the seer than did wolves and shelter dogs. We agree with the authors' position that most of these findings are best explained by preexperime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Dogs may avoid people who are looking at the ceiling, a behaviour that dogs usually do not see in everyday life conditions in association with food provisioning, and for which they therefore have no associations. Pre-experimental learning about human behaviour and its consequences may fully account for the results in the GA test (Gagliardi et al 1995; Roberts and Macpherson 2011; Udell et al 2011; Viranyi and Range 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Dogs may avoid people who are looking at the ceiling, a behaviour that dogs usually do not see in everyday life conditions in association with food provisioning, and for which they therefore have no associations. Pre-experimental learning about human behaviour and its consequences may fully account for the results in the GA test (Gagliardi et al 1995; Roberts and Macpherson 2011; Udell et al 2011; Viranyi and Range 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In their overall performance, dogs did not choose the knower. This drop in accuracy could be attributed to dogs' confused memories of the roles of the knower and guesser in the current trial with memories of the roles they had played on previous trials (Roberts & Macpherson, 2011). Thus, if there was an effect, it was not very strong.…”
Section: Seeing Leads To Knowingmentioning
confidence: 96%
“…Cooper et al (2003) reported that in the first trial 14/15 dogs (93%) chose the location pointed to by the knower (Cooper et al, 2003;Roberts & Macpherson, 2011) and ignored the pointing cue of the guesser. However, as Udell and Wynne (2011) point out, the experiment referred to in Cooper et al (2003) has never been properly published.…”
Section: Seeing Leads To Knowingmentioning
confidence: 98%
“…We are grateful to Roberts and Macpherson (2011) for reminding us of the tantalizing first-trial data related in Cooper et al (2003). Cooper et al summarized results from a version of Povinelli, Nelson and Boysen (1990) "guesser--knower" experiment carried out on 15 dogs.…”
Section: What Is Perspective Taking?mentioning
confidence: 99%
“…Roberts and Macpherson (2011) suggest that alternative experimental designs might have given the theory-of-mind theory of canine behavior a better chance over lower-level interpretations of the animals' behavior. To this end, they suggest that had the "seeing" experimenter turned her back but looked over her shoulder, this might have constituted a more compelling test.…”
Section: What Is Perspective Taking?mentioning
confidence: 99%